Effect of enological tannin addition on astringency subqualities and phenolic content of red wines. Issue 3 (10th April 2018) - Rinaldi, A.; Moio, L.
Abstract: Four Italian red wine varieties (Sangiovese, Montepulciano, Barbera, Nero d'Avola) were used to investigate the effect of enological tannins on astringency characteristics and phenolic content of red wines. Wines were treated with three tannins of different origins (G = grape, E= oak, and P = exotic wood) at two concentrations (10, 20 g/hl) and aged for 1 year. Wines were evaluated for astringency and for 16 subqualities using check‐all‐that‐apply questions. In addition, polymeric pigments, tannins, flavans, total anthocyanins, and color parameters were analyzed. Enological tannin promoted color stability by pigmented polymers formation. Astringency intensity was not enhanced, even better an improvement of mouthfeel sensations was achieved with wood‐derived tannins. Multivariate analysis revealed a great influence of the variety on astringency and phenolic characteristics of wines. Therefore, the initial phenolic composition of wine seems to be the main driver of the evolution of wine during aging. Practical applications: Tannin addition is an enological practice widely widespread because of many economical benefits. The use of enological tannins during aging can contribute to color stabilization and to an improvement of astringency subqualities of wines. Training on astringency subqualities with touch standards coupled with the check‐all‐that‐apply questions can provide an interesting way to reveal the different aspects of red wine astringency. Despite high astringency and high phenolic content, a wine may present desirable subqualities which can improve wine experience. Finally, a tailored use of enological tannins depends on wine variety.